Circulating immunosuppressive cells of prostate cancer patients before and after radical prostatectomy: Profile comparison. (20th February 2013) - Brusa, Davide; Simone, Mariagrazia; Gontero, Paolo; Spadi, Rosella; Racca, Patrizia; Micari, Jasmin; Degiuli, Maurizio; Carletto, Sara; Tizzani, Alessandro; Matera, Lina
Abstract : Objectives: A dendritic cell‐based cancer vaccine has recently received Food and Drug Administration approval in the USA based on its ability to prolong the survival of prostate cancer patients with advanced disease. However, tumor‐mediated immunosuppressive mechanisms might represent an obstacle to optimal performance of this therapy. We have recently shown that monocytes from the blood of prostate cancer patients can fully mature to dendritic cells only after the tumor is removed. Here, we have tested the hypothesis that these tumor‐driven monocytes correspond to the recently described subset of CD14 + HLA‐DR low immunosuppressor cells. Methods: Prostate cancer patients were studied before and 1 month after prostatectomy. Pre‐ and postsurgical patients with colorectal cancer were also included for comparison. Flow cytometric analysis was applied to define CD14 − HLA‐DR low CD33 + CD11b + (myeloid) and CD14 + HLA‐DR low (monocytic) suppressor cells. Interferon‐γ release was used to assess the immunocompetence of lymphocytes. Results: In both prostate cancer and colorectal cancer patients, the percentage of CD14 + HLA‐DR low cells was several‐fold higher compared with normal subjects. This was not the case for CD14 − HLA‐DR low CD33 + CD11b + cells. Furthermore, postsurgical normalization of CD14 + HLA‐DR low cells only occurred in prostate cancer patients. In all patients, the interferon‐γ response of T lymphocytes to phorbolmyristate acetate‐ionomycin was higher compared with normal donors, but it was further increased after tumor ablation only in prostate cancer patients. Conclusions: The direct link between CD14 + HLA‐DR low increase and presence of primary tumor suggests a distinguishing immunosuppressive profile of prostate cancer. This observation supports the principle that the appropriate setting for prostate cancer vaccine therapy is a minimal disease status.